2014
DOI: 10.1063/1.4904402
|View full text |Cite
|
Sign up to set email alerts
|

Generation of high-energy mono-energetic heavy ion beams by radiation pressure acceleration of ultra-intense laser pulses

Abstract: Generation of high-energy mono-energetic heavy ion beams by radiation pressure acceleration (RPA) of intense laser pulses is investigated. Different from previously studied RPA of protons or light ions, the dynamic ionization of high-Z atoms can stabilize the heavy ion acceleration. A selforganized, stable RPA scheme specifically for heavy ion beams is proposed, where the laser peak intensity is required to match with the large ionization energy gap when the successive ionization state passes the noble gas con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…However, acceleration of high Z target ions has an additional layer of complexity due to field and collisional ionization which lead to space-and time-dependent charge state distributions. Efficient acceleration relies on producing highly charged species overlapped in space with the strongest accelerating field; it has been shown that matching the target material with a given laser intensity is key to high energy acceleration for this reason [26]. This additional layer of complexity means the best parameters for accelerating protons are not necessarily best for accelerating high Z ions.…”
Section: Introductionmentioning
confidence: 99%
“…However, acceleration of high Z target ions has an additional layer of complexity due to field and collisional ionization which lead to space-and time-dependent charge state distributions. Efficient acceleration relies on producing highly charged species overlapped in space with the strongest accelerating field; it has been shown that matching the target material with a given laser intensity is key to high energy acceleration for this reason [26]. This additional layer of complexity means the best parameters for accelerating protons are not necessarily best for accelerating high Z ions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SWA can be achieved under a much relaxed experimental condition. This is also in contrast to the radiation pressure acceleration [13][14][15][16][17][18] which is exposed to various transverse instabilities and faces formidable experimental challenges. While for heavy ions with low Z/A, the shock velocity is slow due to the slow ion acoustic wave speed, i.e., = c ZT Am f = Ze A m v 1 2 s p s 2 , indicates the heavy ion reflection requires higher potential barrier given the same shock velocity, which limits the resultant beam density.…”
Section: Introductionmentioning
confidence: 99%
“…The particle number with energy ≥ 100 MeV=u is about 10 10 (charge 20 nC) and the total beam energy is about 7J [4(f)], at least one order larger than Refs. [17,24]. However, for both cases, without ionization and without Au coating, the energy spectra are much broadened due to premature termination of RPA and CE, see the blue and green lines in 4(e).…”
mentioning
confidence: 99%
“…Considering intense lasers at 10 21 -10 22 W=cm 2 , the field ionization rate from Au 50þ to Au 51þ is estimated as P f ≤ 1, while P c < 10 −4 . So the field ionization dominates [24][25][26], where the Au coating is ionized to be Au 51þ . Similarly, the Al foil are estimated to be fully ionized as Al 13þ rapidly.…”
mentioning
confidence: 99%